Gold-supported cerium-doped NiOx catalysts for water oxidation - Garcia Melchor, Max (My University, 2016)
The development of high-performance catalysts for the oxygen evolution reaction (OER) is paramount for cost-effective conversion of renewable electricity to fuels and chemicals. Here we report the significant enhancement of the OER activity of electrodeposited NiOx films resulting from the combined effects of using cerium as a dopant and gold as a metal support. This NiCeOx-Au catalyst delivers high OER activity in alkaline media, and is among the most active OER electrocatalysts reported to date. Based on experimental observations and theoretical modelling, we ascribe the activity to a combination of electronic, geometric and support effects, where highly active under-coordinated sites at the oxide support interface are modified by the local chemical binding environment and by doping the host Ni oxide with Ce. The NiCeOx-Au catalyst is further demonstrated in a device context by pairing it with a nickel-molybdenum hydrogen evolution catalyst in a water electrolyser, which delivers 50 mA consistently at 1.5 V over 24 hours of continuous operation.
PUBLISHED
Keywords: Catalysts; Cerium; Gold; Oxygen evolution reaction; Oxidation